Verbal Violence in Sunni-Shia Debate: Al-Munazarāt Baina Fuqahā' al-Sunnah wa Fuqahā' al-Syi'ah Book Study - Zamzam, Zamzam; Habib, Habib; Al-Hassy, Moh. Ali Qorror (KALAM, 2019)
Sunni – Shia polemic becomes issues depict the debate in Islamic discourse. Even though it starts from political issue, while in its progress meddling in theology area to justify the truth of each other. In this context, verbal violence often occurs to attack, hurt, insult, or weaken the opponent. This paper will discuss verbal violence in the Sunni – Shia polemic as has been written in al-Munazarat baina Fuqaha' as-Sunnah wa Fuqaha' asy-Syi'ah book. The paper focuses on discussing the form and the factor behind these violences. The study is conducted using qualitative descriptive analysis method. The research result shows that the verbal violence found in the text quite varied, which are verbal violence in the form of satire, accuse or defame, mock, intimidate, curse, and threaten. Factors that cause violence also vary. However, the main factor of verbal violence is when the speaker is carried away by the critical situation of the debate. Other influencing factor is the speaker feels proud of himself or group, disappointed, hatred, and power relation. This article concludes that verbal violence can be found in debate on Islamic religious discourse.